Topology and adenocarcinoma cell localization dataset on the labyrinthin diapeutic biomarker - Ankit Sharma; Michael Babich; Tianhong Li; James A. Radosevich (BMC Research Notes, 2023)
Abstract Objective The discovery and characterization of tumor associated antigens is increasingly important to advance the field of immuno-oncology. In this regard, labyrinthin has been implicated as a neoantigen found on the cell surface of adenocarcinomas. Data on the (1) topology, (2) amino acid (a.a.) homology analyses and (3) cell surface localization of labyrinthin by fluorescent activated cell sorter (FACS) are studied in support of labyrinthin as a novel, pan-adenocarcinoma marker. Results Bioinformatics analyses predict labyrinthin as a type II protein with calcium binding domain(s), N-myristoylation sites, and kinase II phosphorylation sites. Sequence homologies for labyrinthin (255 a.a.) were found vs. the intracellular aspartyl/asparaginyl beta-hydroxylase (ASPH; 758 a.a.) and the ASPH-gene related protein junctate (299 a.a.), which are both type II proteins. Labyrinthin was detected by FACS on only non-permeablized A549 human lung adenocarcinoma cells, but not on normal WI-38 human lung fibroblasts nor primary cultures of normal human glandular-related cells. Microscopic images of immunofluorescent labelled MCA 44-3A6 binding to A549 cells at random cell cycle stages complement the FACS results by further showing that labyrinthin persisted on the cell surfaces along with some cell internalization for greater than 20 min.